Mascaramento clínico: limiares auditivos pelos métodos Platô e Otimizado - Fernandes, Kelly Cristina de Souza (2007)
INTRODUCTION: Many situations may difficult the obtaining of thresholds for each ear, separately, in pure tone audiometry, demanding the use of masking. The plateau method, developed by Hood (1960) has being the most utilized for more than four decades. Nevertheless, Turner (2004) has suggested a masking protocol with a different method, called optimized, which could replace the previous one with efficacy in specific cases. PURPOSE: To verify if there is a difference among air and bone conduction hearing thresholds, using the two clinical masking methods: plateau and optimized. METHOD: Forty individuals aged from 15 to 65 years old, with either unilateral or bilateral hearing losses, considering unilateral, bilateral, symmetrical and just bone, proposed by Turner s classification, have participated of this study. They underwent air and bone conduction pure tone audiometry for both ears, without and with the use of the two masking methods. RESULTS: There was a 6.1% difference between the results for the air conduction threshold retest and a 15.1 % for the bone conduction threshold retest, taking into consideration the symmetrical model and a 12.8% for the bone conduction retest, considering the just bone model. There was no statistically significant difference between the air and bone conduction hearing thresholds with the two masking methods, considering unilateral and bilateral models. CONCLUSION: The plateau method can be utilized for all models and the optimized one is the most efficient for unilateral and bilateral models, having no indication for the symmetrical model. Therefore, both masking methods have presented advantages and disadvantages, implying that the audiologist must have knowledge of them in order to choose correctly the masking method to be used